2019
DOI: 10.1037/amp0000408
|View full text |Cite
|
Sign up to set email alerts
|

But what do participants want? Comment on the “Data Sharing in Psychology” special section (2018).

Abstract: This commentary addresses a recent special section on data sharing (i.e., open data) in the February-March 2018 American Psychologist. In 4 articles, the authors outline how open data can positively impact psychology and provide guidelines for adopting open data practices, which we believe is to be commended. However, this special issue has not acknowledged a crucial concern in the open data debate: the views and desires of participants. Participants are the backbone of psychological research and an important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 11 publications
0
10
1
Order By: Relevance
“…In contrast, psychologists who believe that data sharing does not increase the benefits to their research community are hesitant to both share data and adopt open data badges. Psychologists' perceptions about perceived academic reputation and perceived academic risk associated with data sharing did not influence psychologists' intentions to share their data in the present study; these results were surprising given prior studies did indicate academic reputation (Kim & Stanton, 2016; Tenopir et al, 2020) and risk (Cummings & Day, 2019; Houtkoop et al, 2018) as significant data sharing factors. As it pertains to open data badge adoption, perceived academic reputation had a significant positive influence and perceived academic risk had a significant negative influence on psychologists' decision to adopt an open data badge.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…In contrast, psychologists who believe that data sharing does not increase the benefits to their research community are hesitant to both share data and adopt open data badges. Psychologists' perceptions about perceived academic reputation and perceived academic risk associated with data sharing did not influence psychologists' intentions to share their data in the present study; these results were surprising given prior studies did indicate academic reputation (Kim & Stanton, 2016; Tenopir et al, 2020) and risk (Cummings & Day, 2019; Houtkoop et al, 2018) as significant data sharing factors. As it pertains to open data badge adoption, perceived academic reputation had a significant positive influence and perceived academic risk had a significant negative influence on psychologists' decision to adopt an open data badge.…”
Section: Discussioncontrasting
confidence: 88%
“…Another factor that would prohibit researchers from sharing their data involves the effort and time required for making the data interpretable by outside researchers (Kim & Stanton, 2016; Tenopir et al, 2015, 2020). Similarly, Houtkoop et al (2018) and Cummings and Day (2019) also identified psychologists' diverse concerns in data sharing such as loss of control over data, time‐consuming in preparing data, misinterpretation of data, and being scooped. Prior studies identified the norm of data sharing as an important data sharing factor in STEM (Kim & Stanton, 2016) and social sciences (Kim & Adler, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Just as collaboration and discussion are necessary for the application of new methods, technologies, and empirical frameworks, the same processes will continue to result in evolving ethical frameworks that prioritize factors such as integrity, accountability, and fairness. Indeed, psychological research on precisely such topics leaves us nicely positioned to take charge of shaping the future ethical landscape (Cummings & Day, 2019).…”
Section: The Personality Panoramamentioning
confidence: 99%
“…Matters of ‘personality privacy’ are critical not just because they involve values that are deeply felt by many around us, but also because threats to privacy have a range of social and ethical consequences (see Custers et al, 2017 for a comprehensive treatment). If personality includes identity and reputation (Hogan, Hogan, & Roberts, 1996; McAbee & Connelly, 2016), then an increase in the sphere of reputation implies a reduction in the private and personal.…”
Section: The Personality Panoramamentioning
confidence: 99%